On the Meaning of 'Reality' - Code, Murray (Cosmos and History: The Journal of Natural and Social Philosophy, 2022)
Modern physics has revealed the intractability of the problem of interpretation in so-called `exact' science, thus vindicating, at least in part, A. N. Whitehead's highly unorthodox non-modern naturalism. For his attempt to rescue life from modern self-styled naturalists points to the need for a would-be naturalist to `let the dialectic go,' as Victor Lowe put it. That is, to enlist the `method’ of `imaginative generalization' as the proper way to do speculative metaphysics. Whitehead’s reasonings thus in effect illustrate a `living' (or `artful’) reason that renders otiose his elaborate attempt in Process and Reality to construct a systematic, comprehensive theory of actuality based upon a formal categoreal scheme. For his writings actually show how to frame a vitalistic metaphysics based upon a metaphysical imaginary that revolves about the most salient characteristics of a wisely ensouled human self.